Coating solution for forming a positive electrode and its manufacturing method, manufacturing method for a positive electrode, and manufacturing method for a battery

JP2026166798APending Publication Date: 2026-10-14DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059985
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0007】 本開示によれば、導電性を著しく低下させることなく、低粘度化又は高濃度化が容易な、新規な改質カーボンブラックを含む正極形成用塗液、及びその製造方法が提供される。また、本開示によれば、上記正極形成用塗液を用いた正極の製造方法、及び、上記正極形成用塗液を用いた電池の製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166798000001
    Figure 2026166798000001
  • Figure 2026166798000002
    Figure 2026166798000002
Patent Text Reader

Abstract

To provide a coating liquid for forming a positive electrode containing a novel modified carbon black that can be easily made low-viscosity or high-concentration without significantly reducing conductivity, and a method for producing the same. [Solution] The material comprises an active material, a binder, modified carbon black, and a liquid medium, wherein the modified carbon black has a specific surface area (BET(m²)). 2 The ratio of iodine adsorption amount (IV (mg / g)) to iodine adsorption amount (IV / BET) is 0.70 or more and 1.20 or less, and the amount of carbon dioxide released per unit surface area by temperature-controlled desorption gas analysis of the modified carbon black is 2.5 × 10⁻⁶. -7 mol / m 2 The above results show that the amount of carbon monoxide released per unit surface area of ​​the modified carbon black, as measured by temperature-controlled desorption gas analysis, is 5.0 × 10⁻⁶. -7 mol / m 2 The above describes the coating liquid for forming a positive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a coating solution for forming a positive electrode containing modified carbon black, a method for producing the same, a method for producing a positive electrode, and a method for producing a battery. [Background technology]

[0002] Carbon black has traditionally been used in applications such as conductive materials, and the development of carbon black with various characteristic values ​​has been considered (for example, Patent Document 1). [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2009-035598 [Overview of the project] [Problems that the invention aims to solve]

[0004] In recent years, with the diversification of applications for lithium-ion secondary batteries and the like, there has been a demand for diversification in the means and methods of forming the positive electrode, which is one of the components of these batteries.

[0005] This disclosure aims to provide a novel positive electrode forming coating liquid containing modified carbon black that can be easily made low-viscosity or high-concentration without significantly reducing conductivity, and a method for manufacturing the same. Furthermore, this disclosure aims to provide a method for manufacturing a positive electrode using the above positive electrode forming coating liquid, and a method for manufacturing a battery using the above positive electrode forming coating liquid. [Means for solving the problem]

[0006] This disclosure relates, for example, to the following [1] to [9]. [1] It comprises an active material, a binder, modified carbon black, and a liquid medium. The BET specific surface area (BET(m²)) of the modified carbon black. 2 / g)) to the iodine adsorption amount (IV(mg / g)) (IV / BET) is 0.70 or more and 1.20 or less, In the modified carbon black, the release amount of carbon dioxide per unit surface area measured by temperature-programmed desorption gas analysis is 2.5×10 -7 mol / m 2 or more, In the modified carbon black, the release amount of carbon monoxide per unit surface area measured by temperature-programmed desorption gas analysis is 5.0×10 -7 mol / m 2 or more, The coating liquid for forming a positive electrode. [2] In the modified carbon black, the release amount of carbon dioxide per unit surface area measured by temperature-programmed desorption gas analysis is 2.0×10 -6 mol / m 2 or less, In the modified carbon black, the release amount of carbon monoxide per unit surface area measured by temperature-programmed desorption gas analysis is 5.0×10 -6 mol / m 2 or less, the coating liquid for forming a positive electrode according to [1]. [3] The BET specific surface area of the modified carbon black is 120 m 2 / g or more and 500 m 2 / g or less, the coating liquid for forming a positive electrode according to [1] or [2]. [4] The coating liquid for forming a positive electrode according to any one of [1] to [3], wherein the modified carbon black is an ozone-treated product of acetylene black. [5] A coating liquid production step of mixing an active material, a binder, modified carbon black, and a liquid medium to obtain the coating liquid for forming a positive electrode is included, In the modified carbon black, the ratio (IV / BET) of the iodine adsorption amount (IV(mg / g)) to the BET specific surface area (BET(m 2 / g)) is 0.70 or more and 1.20 or less, In the modified carbon black, the release amount of carbon dioxide per unit surface area measured by temperature-programmed desorption gas analysis is 2.5×10 -7 mol / m2 That's all. The carbon monoxide emission per unit surface area of ​​the aforementioned modified carbon black, as measured by temperature-controlled desorption gas analysis, is 5.0 × 10⁻⁶. -7 mol / m 2 That's all. A method for manufacturing a coating solution for forming a positive electrode. [6] The aforementioned coating liquid manufacturing process, A first mixing step involves mixing the powdered modified carbon black with a binder-containing solution containing the binder and solvent to obtain a mixed solution. A second mixing step involves mixing the aforementioned mixture with the aforementioned active material to obtain the coating liquid for forming the positive electrode. The manufacturing method described in [5], including [7] The manufacturing method according to [6], wherein the second mixing step is a step of mixing the mixed liquid, the active material, and the liquid medium to obtain the coating liquid for forming the positive electrode. [8] A method for manufacturing a positive electrode, comprising the step of applying a positive electrode forming coating liquid described in any one of [1] to [4], or a positive electrode forming coating liquid manufactured by the manufacturing method described in any one of [5] to [7], onto a current collector to form a composite material layer on the current collector. [9] A step of applying a positive electrode forming coating liquid described in any one of [1] to [4], or a positive electrode forming coating liquid manufactured by any one of [5] to [7], onto a current collector to form a composite layer on the current collector and obtain a positive electrode, The process of stacking the positive electrode and the negative electrode with a separator in between to obtain a battery, A method for manufacturing batteries, including the invention of a battery. [Effects of the Invention]

[0007] This disclosure provides a coating liquid for forming a positive electrode containing a novel modified carbon black that can be easily made low-viscosity or high-concentration without significantly reducing conductivity, and a method for manufacturing the same. Furthermore, this disclosure provides a method for manufacturing a positive electrode using the above-mentioned coating liquid for forming a positive electrode, and a method for manufacturing a battery using the above-mentioned coating liquid for forming a positive electrode. [Modes for carrying out the invention]

[0008] Preferred embodiments of this disclosure will be described in detail below. In this specification, carbon black may be abbreviated as "CB" and carbon nanotube as "CNT". In this specification, the tilde symbol "~" is used to indicate a numerical range including the numbers before and after it. Specifically, "X~Y" (where X and Y are both numerical values) means "X or greater and Y or less".

[0009] (Coating liquid for positive electrode formation) The coating solution for forming the positive electrode in this embodiment comprises an active material, a binder, modified carbon black, and a liquid medium. In this embodiment, the BET specific surface area (BET(m²)) of the modified carbon black is 2 The ratio of iodine adsorption amount (IV (mg / g)) to iodine adsorption amount (IV / BET) is between 0.70 and 1.20. Furthermore, the amount of carbon dioxide released per unit surface area from the modified carbon black, as measured by temperature-controlled desorption gas analysis, is 2.5 × 10⁻⁶. -7 mol / m 2 That concludes the report. Furthermore, the amount of carbon monoxide released per unit surface area from modified carbon black, as measured by temperature-controlled desorption gas analysis, is 5.0 × 10⁻⁶. -7 mol / m 2 That's all.

[0010] In this embodiment, because the modified carbon black exhibits excellent dispersibility in liquid media, the viscosity is lower at the same solid content concentration compared to when conventional carbon black is used. Furthermore, in this embodiment, a higher solid content concentration can be achieved at a similar viscosity compared to when conventional carbon black is used.

[0011] In this embodiment, the ratio (IV / BET) can be said to be an indicator of the amount of iodine adsorbed per unit surface area. Furthermore, since the adsorption of iodine is inhibited if acidic functional groups (carboxyl groups) are present on the surface of carbon black, in this embodiment, the ratio (IV / BET) can also be said to be used to evaluate the proportion of acidic functional groups present. In other words, the modified carbon black of this embodiment is carbon black that has been modified so that the ratio (IV / BET) falls within the above range, and it can be said that it has acidic functional groups on its surface in a certain proportion.

[0012] The modified carbon black of this embodiment has a certain proportion of acidic functional groups on its surface, which improves its affinity with liquid media. Furthermore, the repulsion between the acidic functional groups makes it easier to resolve aggregated states. For these reasons, it is believed that a suitable dispersion state is maintained in the coating solution for forming the positive electrode, resulting in lower viscosity.

[0013] Furthermore, in this embodiment, the amount of carbon dioxide released and the amount of carbon monoxide released can be said to be indicators of the amount of oxygen-containing groups formed on the surface of the modified carbon black. In other words, if the amount of carbon dioxide released and the amount of carbon monoxide released are above a predetermined amount, it means that an amount of oxygen-containing groups greater than or equal to a predetermined amount is formed on the surface of the modified carbon black. In this embodiment, it is believed that the formation of oxygen-containing groups on the surface of the modified carbon black improves its affinity with liquid media, dispersants, binders, etc., resulting in a lower viscosity coating solution for cathode formation.

[0014] Note that oxygen-containing groups also include acidic functional groups. However, oxygen-containing groups other than acidic functional groups have little effect in inhibiting iodine adsorption. In other words, the modified carbon black of this embodiment has an amount of oxygen-containing groups on its surface that is greater than a predetermined amount, while the amount of acidic functional groups is kept to a level where the ratio (IV / BET) is 0.70 or higher. Therefore, in this embodiment, the decrease in electrical conductivity caused by the presence of acidic functional groups is suppressed, and good battery characteristics can be achieved.

[0015] The positive electrode forming coating liquid of this embodiment may be used to form a positive electrode comprising a current collector and an asphalt mixture layer on a current collector.

[0016] The components of the coating solution for forming the positive electrode in this embodiment will be described in detail below.

[0017] (Modified carbon black) The modified carbon black of this embodiment is a carbon material in which at least a portion of carbon black has been modified.

[0018] The BET specific surface area of ​​modified carbon book is, for example, 120 m². 2 It may be 150m or more / g 2 / g or more, 200m 2 / g or more, 250m 2 / g or more, or 300m 2 It may be more than / g. The BET specific surface area of ​​modified carbon black is, for example, 500m². 2 It may be less than or equal to / g, and 450m 2 / g or less, 400m 2 / g or less, or 350m 2 It may be less than / g. Within this range, the effects described above are more pronounced.

[0019] The BET specific surface area of ​​modified carbon black is measured using nitrogen as the adsorbate and in accordance with JIS Z8830.

[0020] The amount of iodine adsorbed by the modified carbon black may be, for example, 80 mg / g or more, 100 mg / g or more, 120 mg / g or more, or 140 mg / g or more. The amount of iodine adsorbed by the modified carbon black may be, for example, 500 mg / g or less, 450 mg / g or less, 420 mg / g or less, or 400 mg / g or less. This will result in a more pronounced effect than described above.

[0021] The amount of iodine adsorbed by modified carbon black is measured using iodine as the adsorbate, in accordance with JIS K1474.

[0022] The ratio of modified carbon black (IV / BET) is 0.70 or higher, and may be 0.80 or higher, 0.85 or higher, or 0.90 or higher from the viewpoint of further improving conductivity and making it more suitable for conductive material applications. Alternatively, the ratio of modified carbon black (IV / BET) is 1.20 or lower, and may be 1.15 or lower, 1.10 or lower, or 1.05 or lower from the viewpoint of further improving dispersibility.

[0023] The amount of carbon dioxide emitted per unit surface area in modified carbon black, as measured by thermal desorption gas analysis (TDS), is 2.5 × 10⁻⁶. -7 mol / m 2 That concludes the discussion. From the perspective of further improving diversification, 3.0 × 10 -7 mol / m 2 The above is 3.5 × 10 -7 mol / m 2 The above, or 3.7 × 10 -7 mol / m 2 The amount of carbon dioxide released may be, for example, 2.0 × 10⁻⁶. -6 mol / m 2 The following may be used, and from the viewpoint of further improving conductivity and making it more suitable for conductive material applications, 1.5 × 10 -6 mol / m 2 Below, 1.2 × 10 -6 mol / m 2 The following, or 1.0 × 10 -6 mol / m 2 The following is also acceptable.

[0024] The amount of carbon monoxide released per unit surface area in modified carbon black, as measured by thermal desorption gas analysis (TDS), is 5.0 × 10⁻⁶. -7 mol / m 2 That concludes the discussion. From the perspective of further improving variance, 7.0 × 10 -7 mol / m 2 The above is 9.0 x 10 -7 mol / m 2 The above, or 1.1 × 10 -6 mol / m 2 The amount of carbon monoxide released may be, for example, 5.0 × 10⁻⁶.-6 mol / m 2 The following may be used, and from the viewpoint of further improving conductivity and making it more suitable for conductive material applications, 4.5 × 10 -6 mol / m 2 Below, 4.0 × 10 -6 mol / m 2 The following, or 3.8 × 10 -6 mol / m 2 The following is also acceptable.

[0025] In modified carbon black, the amount of water (H2O) released per unit surface area, as measured by thermal desorption gas analysis (TDS), is, for example, 1.0 × 10⁻⁶. -7 mol / m 2 The above is sufficient, and from the viewpoint of further improving variance, 1.1 × 10 -7 mol / m 2 The above is 1.2 × 10 -7 mol / m 2 The above, or 1.4 × 10 -7 mol / m 2 The above is also acceptable. Furthermore, the amount of water (H2O) released is, for example, 5.0 × 10⁻⁶. -7 mol / m 2 The following may be used, and from the viewpoint of further improving conductivity and making it more suitable for conductive material applications, 4.5 × 10 -7 mol / m 2 Below, 4.0 × 10 -7 mol / m 2 The following, or 3.5 × 10 -7 mol / m 2 The following is also acceptable.

[0026] In this specification, the measurement of thermal desorption gas analysis (TDS) and the calculation of the release amounts of each component shall be performed by the following method. One mg of the powder to be measured is weighed into a quartz dish, a quartz lid is placed on top, and the temperature is raised from room temperature to 1300°C. The desorbed gas is then analyzed using a quadrupole mass spectrometer (QMS). The desorbed amounts of carbon dioxide, carbon monoxide, and water are calculated based on sensitivity correction using the ESCO method, assuming that the ion current in the mass spectrum m / z originates only from the target molecules. The calculated desorbed amount (mol / mg) is then calculated using the BET specific surface area (m²) of the sample being measured. 2Using the value of / g, 1m 2 Convert to moles per unit. Desorption amount of carbon dioxide and carbon monoxide (mol / m³) 2 The amounts are calculated from the amount of water removed from room temperature to 1300°C. 2 To exclude the effect of adsorbed moisture, the amount of desorption is calculated from the amount of desorption between 150°C and 1300°C.

[0027] The modified carbon black of this embodiment may be, for example, an ozone-treated carbon black (hereinafter also referred to as raw material carbon black). That is, the modified carbon black of this embodiment may be manufactured by ozone-treating raw material carbon black.

[0028] (Method for manufacturing modified carbon black) The modified carbon black of this embodiment may be produced by a manufacturing method that includes a surface treatment step to obtain modified carbon black by ozone treatment of raw material carbon black.

[0029] The raw material carbon black may be, for example, acetylene black, furnace black, channel black, etc., and from the viewpoint of easily obtaining modified carbon black that satisfies the above numerical range, acetylene black may be used. The proportion of acetylene black in the raw material carbon black may be, for example, 80% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, or 99% by mass or more, or 100% by mass.

[0030] The BET specific surface area (BET) of raw carbon black is, for example, 100m². 2 It may be 150m or more, and from the viewpoint of making it easier to obtain modified carbon black having the above-mentioned characteristics, 2 / g or more, 200m 2 / g or more, or 250m 2 It may be more than / g. The BET specific surface area of ​​the raw material carbon black is, for example, 400m². 2 / g or less, and from the viewpoint of facilitating the obtainment of modified carbon black having the above properties, it may be 370m 2 / g or less, 350m 2 / g or less, or 330m 2 / g or less.

[0031] The BET specific surface area of the raw material carbon black is measured by a method conforming to JIS Z8830 using nitrogen as the adsorbate.

[0032] The BET specific surface area of modified carbon black tends to be larger than the BET specific surface area of raw material carbon black. The ratio (S1 / S0) of the BET specific surface area (S1) of modified carbon black to the BET specific surface area (S0) of raw material carbon black may be, for example, 1.05 or more, and may be 1.08 or more, 1.10 or more, or 1.15 or more. In addition, the above ratio (S1 / S0) may be, for example, 1.5 or less, and may be 1.4 or less, 1.3 or less, or 1.2 or less.

[0033] The ozone treatment may be performed, for example, such that the ratio (S1 / S0) falls within the above range.

[0034] The iodine adsorption value (IV) of the raw material carbon black may be, for example, 100 mg / g or more, and from the viewpoint of facilitating the obtainment of modified carbon black having the above properties, it may be 130 mg / g or more, 150 mg / g or more, or 200 mg / g or more. The iodine adsorption value of the raw material carbon black may be, for example, 400 mg / g or less, and from the viewpoint of facilitating the obtainment of modified carbon black having the above properties, it may be 350 mg / g or less, 300 mg / g or less, or 250 mg / g or less.

[0035] The iodine adsorption value of the raw material carbon black is measured by the same method as the iodine adsorption value of modified carbon black.

[0036] The ratio (IV / BET) of the raw material carbon black may be, for example, 1.15 or higher, and from the viewpoint of facilitating the obtainment of modified carbon black having the above-described characteristics, it may be 1.17 or higher, 1.20 or higher, or 1.25 or higher. Further, the ratio (IV / BET) of the raw material carbon black may be, for example, 1.45 or lower, and from the viewpoint of facilitating the obtainment of modified carbon black having the above-described characteristics, it may be 1.40 or lower, 1.35 or lower, or 1.30 or lower.

[0037] The ratio (IV / BET) of the modified carbon black tends to be smaller than the ratio (IV / BET) of the raw material carbon black. The ratio (R1 / R0) of the ratio (IV / BET) (R1) of the modified carbon black to the ratio (IV / BET) (R0) of the raw material carbon black may be, for example, 0.97 or lower, and may be 0.95 or lower, 0.93 or lower, or 0.90 or lower. Further, the ratio (R1 / R0) may be, for example, 0.50 or higher, and may be 0.55 or higher, 0.60 or higher, or 0.65 or higher.

[0038] The ozone treatment may be performed, for example, such that the ratio (R1 / R0) falls within the above range.

[0039] The release amount of carbon dioxide per unit surface area measured by temperature-programmed desorption gas analysis (TDS) in the raw material carbon black may be, for example, 4.5×10 -8 mol / m 2 or less, and may be 4.0×10 -8 mol / m 2 or less, 3.5×10 -8 mol / m 2 or less, or 3.0×10 -8 mol / m 2 or less. Further, in the raw material carbon black, the lower limit of the release amount of carbon dioxide is not particularly limited, and may be, for example, 1.0×10 -7 mol / m 2 or more, and may be 1.2×10 -7 mol / m 2 or more.

[0040] The amount of carbon monoxide released per unit surface area from raw carbon black, as measured by thermal desorption gas analysis (TDS), is, for example, 6.0 × 10⁻⁶. -7 mol / m 2 The following may be true: 5.0 × 10 -7 mol / m 2 Below, 4.5 × 10 -7 mol / m 2 The following, or 4.0 × 10 -7 mol / m 2 The following may also apply. Furthermore, the lower limit of carbon monoxide emissions in the raw material carbon black is not particularly limited, for example, 0.5 × 10 -7 mol / m 2 The above is sufficient, 1.0 × 10 -7 mol / m 2 That's fine too.

[0041] The amount of water (H2O) released per unit surface area from raw carbon black, as measured by thermal desorption gas analysis (TDS), is, for example, 0.8 × 10⁻⁶. -7 mol / m 2 The above is sufficient, 0.9 × 10 -7 mol / m 2 The above is 1.0 × 10 -7 mol / m 2 The above, or 1.0 × 10 -7 mol / m 2 The above is also acceptable. Furthermore, in the raw material carbon black, the amount of water (H2O) released is, for example, 5.0 × 10⁻⁶. -7 mol / m 2 The following may be used: 4.5 × 10 -7 mol / m 2 Below, 4.0 × 10 -7 mol / m 2 The following, or 3.5 × 10 -7 mol / m 2 The following is also acceptable.

[0042] In this specification, the measurement of thermal desorption gas analysis (TDS) in raw material carbon black, and the calculation of the release amounts of each component, shall be performed using the same method as for modified carbon black.

[0043] The crystallite size (Lc) of the raw material carbon black may be, for example, 10 Å or more, and may be 12 Å or more, 13 Å or more, or 14 Å or more, from the viewpoint of making it easier to obtain modified carbon black with higher conductivity. The crystallite size (Lc) of the raw material carbon black may be, for example, 40 Å or less, and may be 35 Å or less, 30 Å or less, or 25 Å or less, from the viewpoint of making it easier to obtain modified carbon black with better dispersibility.

[0044] In this specification, crystallite size (Lc) is measured in accordance with JIS R7651. Note that the crystallite size (Lc) of carbon black refers to the crystallite size in the c-axis direction of the carbon black crystal layer.

[0045] The average primary particle size of the raw carbon black may be, for example, 5 nm or more, and may be 10 nm or more, 15 nm or more, or 17 nm or more, from the viewpoint of making it easier to obtain modified carbon black with better dispersibility. The average primary particle size of the raw carbon black may be, for example, 30 nm or less, and may be 25 nm or less, 23 nm or less, or 20 nm or less, from the viewpoint of making it easier to obtain modified carbon black with higher conductivity.

[0046] In this specification, the average primary particle diameter of carbon black refers to the average value of the equivalent circle diameter measured based on images obtained by observing carbon black with a transmission electron microscope (TEM). Specifically, it is obtained by taking 10 images of carbon black at a magnification of 100,000x using a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.), measuring the equivalent circle diameter of 200 randomly selected primary particles of carbon black from the obtained images by image analysis, and taking the arithmetic mean.

[0047] Ozone treatment in the surface treatment process may be carried out, for example, by bringing the raw material carbon black into contact with ozone.

[0048] The conditions for ozone treatment are not particularly limited and can be any conditions under which modified carbon black can be obtained from the raw material carbon black as described above. In other words, in the surface treatment process, the conditions for ozone treatment may be adjusted as appropriate so that modified carbon black can be obtained from the raw material carbon black as described above.

[0049] The temperature during ozone treatment may be, for example, 70°C or lower, 60°C or lower, 50°C or lower, or 40°C or lower, from the viewpoint of avoiding a significant increase in the BET specific surface area and making it easier to obtain modified carbon black with the above-mentioned characteristics. Furthermore, from the viewpoint of making temperature control easier, the temperature during ozone treatment may be, for example, 0°C or higher, 10°C or higher, or 20°C or higher.

[0050] Ozone treatment may be carried out, for example, by bringing powdered carbon black into contact with ozone in the gas phase. In other words, the surface treatment step may be a step of ozone treatment of carbon black by bringing powdered carbon black into contact with ozone in the gas phase.

[0051] Ozone treatment may be carried out, for example, by introducing a reaction gas containing ozone into a reaction vessel containing carbon black (preferably in powder form). The reaction vessel can be any vessel capable of stirring the raw material carbon black. The reaction vessel may be, for example, a cylindrical reaction vessel capable of stirring its contents by rotation.

[0052] The amount of ozone supplied in the ozone treatment is not particularly limited; it should be an amount sufficient to obtain modified carbon black with the above-mentioned properties from the aforementioned raw material carbon black.

[0053] The ratio (M1 / S0) of the amount of ozone (M1) supplied into the reaction vessel containing raw material carbon black to the BET specific surface area (S0) of the raw material carbon black in the reaction vessel is, for example, 0.1 mg / m². 2 The above is sufficient, and 0.2 mg / m² 2 More than 0.3mg / m 2 Above, or 0.4 mg / m² 2The above ratio may also be greater than or equal to 1.3 mg / m². Furthermore, the above ratio (M1 / S0) can be, for example, 1.3 mg / m². 2 The following may be used: 1.2 mg / m² 2 Below 1.1mg / m 2 The following, or 1.0 mg / m² 2 The following is also acceptable.

[0054] The content of modified carbon black in the coating solution for forming the positive electrode may be, for example, 0.1% by mass or more, based on the total amount of solids, 0.3% by mass or more, 0.5% by mass or more, 0.7% by mass or more, 0.9% by mass or more, or 1% by mass or more. Alternatively, the content of modified carbon black in the coating solution for forming the positive electrode may be, for example, 10% by mass or less, based on the total amount of solids, 7% by mass or less, 5% by mass or less, or 3% by mass or less.

[0055] (active material) The active material (positive electrode active material) is not particularly limited and can be any material capable of reversibly intercalating and deintercalating cations. For example, the active material may have a volume resistivity of 1 × 10⁻⁶. 4 This may be a lithium-containing composite oxide or lithium-containing polyanionic compound containing manganese of Ω·cm or more. Examples of manganese-containing lithium-containing composite oxides include LiMnO2, LiMnO3, LiMn2O3, Li 1+x Mn 2-x Lithium manganese oxide such as O4 (where x = 0 to 0.33); LiMn x Ni y Co z O2 (however, x+y+z=1, 0≦y<1, 0≦z<1, 0≦x<1), Li 1+x Mn 2-x-y M y O4 (where x = 0 to 0.33, y = 0 to 1.0, 2-xy > 0), LiMn 2-x M xExamples of composite oxides containing one or more transition metal elements include O2 (where x = 0.01 to 0.1) and Li2Mn3MO8. Examples of lithium-containing polyanionic compounds include LiFePO4, LiMnPO4, and Li2MPO4F (where M is at least one metal selected from Co, Ni, Fe, Cr, and Zn). In each compositional formula, M is at least one selected from the group consisting of Fe, Co, Ni, Al, Cu, Mg, Cr, Zn, and Ta.

[0056] Average particle size of the active material (D 50 The average particle size of the active material (D) may be, for example, 3 μm or larger, and may be 5 μm or larger, 10 μm or larger, or 20 μm or larger. 50 ) may be, for example, 45 μm or less, and may be 40 μm or less, 35 μm or less, or 30 μm or less.

[0057] Average particle size of the active material (D 50 ) is measured by laser light scattering.

[0058] The content of the active material in the coating solution for forming the positive electrode may be, for example, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more, based on the total amount of solids. The content of the active material in the coating solution for forming the positive electrode may be, for example, 99.8% by mass or less, 99.5% by mass or less, 99% by mass or less, or 98% by mass or less, based on the total amount of solids.

[0059] (Binding agent) Examples of binders include polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene copolymer, and (meth)acrylic acid ester copolymer. The polymer structure of the binder may be, for example, random copolymer, alternating copolymer, graft copolymer, or block copolymer. From the viewpoint of excellent dielectric strength, polyvinylidene fluoride is preferred as the binder.

[0060] The binder content in the coating solution for forming the positive electrode may be, for example, 0.1% by mass or more based on the total amount of solids, and from the viewpoint of further improving the bonding properties of the composite layer and further improving battery performance, it may be 0.3% by mass or more, 0.5% by mass or more, 0.7% by mass or more, 0.9% by mass or more, or 1% by mass or more. Alternatively, the binder content in the coating solution for forming the positive electrode may be, for example, 10% by mass or less based on the total amount of solids, and from the viewpoint of making it easier to obtain higher conductivity, it may be 7% by mass or less, 5% by mass or less, or 3% by mass or less.

[0061] (Liquid medium) The liquid medium can be any liquid medium capable of dispersing the modified carbon black, binder, and active material. Examples of liquid mediums include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, and methyl isobutyl ketone. Of these, N-methyl-2-pyrrolidone is preferred from the viewpoint of easy dispersibility of carbon black. In this specification, N-methyl-2-pyrrolidone may be abbreviated as "NMP".

[0062] The content of the liquid medium in the coating solution for forming the positive electrode is not particularly limited, and may be adjusted as appropriate, for example, so that the solid content concentration of the coating solution for forming the positive electrode falls within the range described below.

[0063] (Dispersant) The coating solution for forming the positive electrode in this embodiment may further contain a dispersant.

[0064] The dispersant can be any component that has the function of assisting in the dispersion of modified carbon black in a liquid medium. The dispersant can also be called a dispersant for dispersing carbon black in a liquid medium, or a dispersant for carbon black, etc.

[0065] Examples of dispersants include high-molecular-weight dispersants and low-molecular-weight dispersants. From the viewpoint of the long-term dispersion stability of modified carbon black, high-molecular-weight dispersants are preferred.

[0066] The polymeric dispersant can be any polymer that functions as a dispersant. Examples of polymeric dispersants include vinyl polymers having polar groups, carboxymethylcellulose and its salts. Such polymeric dispersants are preferred from the viewpoint of having high affinity for both modified carbon black and liquid media and excellent dispersing function.

[0067] Examples of polar groups include hydroxyl groups, acetyl groups, amino groups, amide groups, acetal groups, oxycarbonyl groups, and nitrile groups. Vinyl polymers preferably have at least one polar group selected from the group consisting of hydroxyl groups, acetyl groups, amino groups, and oxycarbonyl groups, and it is preferable that they have hydroxyl groups. Hydroxyl groups are preferred from the viewpoint of having excellent voltage resistance and being resistant to decomposition even after repeated charging and discharging.

[0068] Examples of vinyl polymers having polar groups include polyvinyl alcohol, polyvinyl acetal (e.g., polyvinyl butyral, polyvinyl formal, etc.), polyvinylpyrrolidone, polyvinylamine, polyvinyl acetate, and polyacrylonitrile. Of these, polyvinyl alcohol and polyvinylpyrrolidone are preferred from the viewpoint of high solubility in NMP and adsorption to modified carbon black, and polyvinyl alcohol is more preferred from the viewpoint of having excellent voltage resistance and hydroxyl groups that are not easily decomposed even after repeated charging and discharging.

[0069] When the coating liquid for forming the positive electrode contains a dispersant, the amount of dispersant in the coating liquid may be, for example, 1 part by mass or more, 5 parts by mass or more, 7 parts by mass or more, or 10 parts by mass or more, per 100 parts by mass of modified carbon black. Alternatively, the amount of dispersant in the coating liquid for forming the positive electrode may be, for example, 35 parts by mass or less, 30 parts by mass or less, 25 parts by mass or less, or 20 parts by mass or less, per 100 parts by mass of modified carbon black. The coating liquid for forming the positive electrode does not need to contain a dispersant, and the amount of dispersant in the coating liquid may be 0 parts by mass per 100 parts by mass of modified carbon black.

[0070] (Other ingredients) The coating solution for forming the positive electrode in this embodiment may further contain other components besides modified carbon black, active material, binder, liquid medium, and dispersant. Examples of other components include carbon nanotubes, graphite, graphene, binder, dispersion stabilizer, defoaming agent, and the like.

[0071] The content of other components may be, for example, 50 parts by mass or less, 45 parts by mass or less, 40 parts by mass or less, or 35 parts by mass or less, or even 0 parts by mass, per 100 parts by mass of modified carbon black.

[0072] The solid content concentration of the coating liquid for forming the positive electrode is not particularly limited, and any solid content concentration that results in a viscosity that allows for the formation of an asphalt mixture layer, i.e., a viscosity that allows for coating onto the current collector, is acceptable. The solid content concentration of the coating liquid for forming the positive electrode may be, for example, 40% by mass or more, 50% by mass or more, 55% by mass or more, or 60% by mass or more. Alternatively, the solid content concentration of the coating liquid for forming the positive electrode may be, for example, 95% by mass or less, 90% by mass or less, 85% by mass or less, or 80% by mass or less.

[0073] The solid component of the positive electrode forming coating solution may be, for example, the remainder after removing the liquid medium from the positive electrode forming coating solution, and may include modified carbon black, an active material, and a binder, and may further include a dispersant.

[0074] The coating solution for forming the positive electrode in this embodiment may be manufactured, for example, by the following manufacturing method.

[0075] (Method for manufacturing a coating solution for forming a positive electrode) The method for producing a coating solution for forming a positive electrode according to this embodiment includes a coating solution manufacturing step of mixing an active material, a binder, modified carbon black, and a liquid medium to obtain a coating solution for forming a positive electrode.

[0076] In the method for manufacturing the coating solution for forming a positive electrode according to this embodiment, the active material, binder, modified carbon black, and liquid medium can be exemplified by those described above.

[0077] The coating liquid manufacturing process may include, for example, a first mixing step of mixing powdered modified carbon black with a binder-containing solution containing a binder and a solvent to obtain a mixed liquid, and a second mixing step of mixing the mixed liquid with an active material to obtain a coating liquid for forming a positive electrode.

[0078] Conventionally, carbon black is usually in powder form, making uniform mixing with other components difficult. Therefore, a known method involves pre-dispersing the carbon black in a liquid medium to create a slurry before mixing it with other components. In contrast, in the coating liquid manufacturing method of this embodiment, the modified carbon black exhibits excellent dispersibility in liquid media. Therefore, even when mixed with a binder-containing solution in powder form, the modified carbon black is dispersed in the mixture in a suitable dispersion state. Consequently, in this embodiment, it is not necessary to slurry the modified carbon black alone, and a coating liquid for cathode formation can be easily manufactured in a short number of steps.

[0079] The binder-containing solution may contain both a binder and a solvent. Examples of solvents include those that are the same as the liquid medium in the slurry described above.

[0080] The solid content concentration of the binder-containing solution is not particularly limited and may be, for example, 0.3% by mass or more. From the viewpoint of further improving the bonding properties of the positive electrode plate and achieving superior cycle characteristics, it may be 0.5% by mass or more, 1% by mass or more, or 1.5% by mass or more. The binder content may be, for example, 5% by mass or less based on the total mass of solid content in the positive electrode composition. From the viewpoint of further reducing the resistance of the positive electrode plate and further improving the discharge rate characteristics, it may be 4.5% by mass or less, 4% by mass or less, or 3.5% by mass or less.

[0081] The first mixing step may consist of mixing only the powdered modified carbon black and the binder-containing solution, or it may also include a step of further mixing in a dispersant. Examples of dispersants are the same as those mentioned above.

[0082] The second mixing step may consist of mixing only the mixed liquid and the active material, or it may also involve further mixing of a liquid medium. In the second mixing step, the viscosity and solid content concentration of the positive electrode forming coating solution may be adjusted by mixing in the liquid medium.

[0083] The mixing method in the coating liquid manufacturing process (first mixing step and second mixing step) is not particularly limited and may be carried out by known methods (for example, stirring and mixing using a bead mill, ball mill, sand mill, twin-screw kneader, orbital agitator, planetary mixer, disper mixer, etc.). These methods and apparatus may also be used in combination as appropriate.

[0084] According to the coating liquid for forming a positive electrode of this embodiment, a composite layer composed of a positive electrode composition can be formed.

[0085] (Positive electrode composition) The positive electrode composition of this embodiment comprises the modified carbon black described above, an active material, and a binder. The positive electrode composition of this embodiment may further contain a dispersant.

[0086] The positive electrode composition of this embodiment may be a composition that constitutes an asphalt layer disposed on a current collector. A positive electrode comprising an asphalt layer composed of the positive electrode composition of this embodiment can be suitably used, for example, as a positive electrode for a lithium-ion secondary battery.

[0087] In the positive electrode composition of this embodiment, the active material, binder, and dispersant can be exemplified by those described above.

[0088] The content of modified carbon black in the positive electrode composition may be, for example, 0.1% by mass or more, and may be 0.3% by mass or more, 0.5% by mass or more, 0.7% by mass or more, 0.9% by mass or more, or 1% by mass or more. Alternatively, the content of modified carbon black in the positive electrode composition may be, for example, 10% by mass or less, and may be 7% by mass or less, 5% by mass or less, or 3% by mass or less.

[0089] The content of the active material in the positive electrode composition may be, for example, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more. Alternatively, the content of the active material in the positive electrode composition may be, for example, 99.8% by mass or less, 99.5% by mass or less, 99% by mass or less, or 98% by mass or less.

[0090] The binder content in the positive electrode composition may be, for example, 0.1% by mass or more, and from the viewpoint of further improving the bonding properties of the composite layer and thus improving battery performance, it may be 0.3% by mass or more, 0.5% by mass or more, 0.7% by mass or more, 0.9% by mass or more, or 1% by mass or more. Alternatively, the binder content in the positive electrode composition may be, for example, 10% by mass or less, and from the viewpoint of making it easier to obtain higher conductivity, it may be 7% by mass or less, 5% by mass or less, or 3% by mass or less.

[0091] When the positive electrode composition contains a dispersant, the amount of dispersant in the positive electrode composition may be, for example, 1 part by mass or more, 5 parts by mass or more, 7 parts by mass or more, or 10 parts by mass or more, per 100 parts by mass of modified carbon black. Alternatively, the amount of dispersant in the positive electrode composition may be, for example, 35 parts by mass or less, 30 parts by mass or less, 25 parts by mass or less, or 20 parts by mass or less, per 100 parts by mass of modified carbon black.

[0092] (Method of manufacturing the positive electrode) The method for manufacturing the positive electrode of this embodiment includes the step (1-1) of applying the positive electrode forming coating liquid described above or the positive electrode forming coating liquid manufactured by the above manufacturing method onto a current collector to form a composite material layer on the current collector.

[0093] The positive electrode comprises a current collector and an asphalt mixture layer. The asphalt mixture layer contains the modified carbon black described above.

[0094] The composite layer may contain the above-described positive electrode composition, or may be composed of the above-described positive electrode composition. The composite layer may also be formed by applying and drying the above-described positive electrode forming coating liquid, and may contain the solid components of the above-described positive electrode forming coating liquid.

[0095] The current collector is not particularly limited, and known current collectors can be used without any particular restrictions. For example, metal foil (metals such as gold, silver, copper, platinum, aluminum, iron, nickel, chromium, manganese, lead, tungsten, and titanium, and alloys mainly composed of any one of these) can be used as the current collector. Among these, it is preferable to use aluminum for the positive electrode and copper for the negative electrode. The current collector is generally provided in the form of foil, but is not limited to this, and perforated foil and mesh-type current collectors can also be used.

[0096] The method for applying the positive electrode forming coating onto the current collector is not particularly limited and may include, for example, die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic coating.

[0097] The amount of coating liquid for forming the positive electrode is not particularly limited and may be adjusted as appropriate so that the thickness of the composite layer is within the desired range.

[0098] The composite layer may be formed by removing at least a portion of the liquid medium from the coating film of the positive electrode forming solution formed on the current collector. The method for removing the liquid medium (drying method) is not particularly limited, and examples of methods that remove at least a portion of the liquid medium by vaporizing it through heating and / or reduced pressure include standing drying, forced-air drying, hot-air drying, infrared heating, far-infrared heating, etc.

[0099] The method for manufacturing the positive electrode of this embodiment may further include a pressurizing step (step (1-2)) in which the composite layer and the current collector are pressed in the lamination direction. The pressurizing step can improve the adhesion between the composite layer and the current collector.

[0100] The pressurizing method used in the pressurizing process is not particularly limited and may include methods such as roll pressing, die pressing, and calendering.

[0101] The thickness of the composite layer in the positive electrode is not particularly limited and may be, for example, 50 μm or more. From the viewpoint of increasing the battery capacity, it is preferably 55 μm or more, more preferably 60 μm or more, and may be 65 μm or more or 70 μm or more. Furthermore, the thickness of the composite layer in the positive electrode may be, for example, 150 μm or less. From the viewpoint of further improving the discharge rate characteristics, it is preferably 140 μm or less, more preferably 130 μm or less, and may be 120 μm or less or 110 μm or less.

[0102] The positive electrode obtained by the manufacturing method of this embodiment can be suitably used as the positive electrode of a battery, particularly a secondary battery (lithium-ion secondary battery).

[0103] (Battery manufacturing method) The battery manufacturing method of this embodiment includes the steps of obtaining a positive electrode by the manufacturing method described above (2-1) and obtaining a battery by stacking the positive electrode and the negative electrode with a separator in between (2-2). The battery may be a secondary battery, and may be a lithium-ion secondary battery.

[0104] In this embodiment, the components of the battery other than the positive electrode may be the same as those of known batteries.

[0105] The battery may, for example, include the positive electrode, negative electrode, and separator described above.

[0106] The separator is not particularly limited, and any separator known as a separator for lithium-ion secondary batteries can be used without any particular restriction. Examples of separators include synthetic resins such as polyethylene and polypropylene. The separator is preferably a porous film because it has good electrolyte retention properties.

[0107] The negative electrode is not particularly limited, and any negative electrode known as a negative electrode for lithium-ion secondary batteries can be used without any particular restriction. The negative electrode may, for example, comprise a negative electrode composite layer containing a negative electrode active material and a binder, and a negative electrode current collector.

[0108] The battery may, for example, include an electrode group in which a positive electrode and a negative electrode are stacked or wound together with a separator in between. That is, step (2-2) may be a step of forming an electrode group in which a positive electrode and a negative electrode are stacked or wound together with a separator in between to obtain a battery.

[0109] In this embodiment, the battery may have, for example, a positive electrode, a negative electrode, and a separator immersed in an electrolyte.

[0110] The electrolyte is not particularly limited and may be, for example, a non-aqueous electrolyte containing a lithium salt. Examples of non-aqueous solvents in a non-aqueous electrolyte containing a lithium salt include ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, and methyl ethyl carbonate. Examples of lithium salts that can be dissolved in a non-aqueous solvent include lithium hexafluoride phosphate, lithium borotetrafluoride, and lithium trifluoromethanesulfonate. The battery may also use an ion-conducting polymer or the like as the electrolyte.

[0111] The battery of this embodiment is not particularly limited in its applications and can be used in a wide range of fields, such as portable AV equipment including digital cameras, video cameras, portable audio players, portable LCD TVs, portable information terminals such as notebook computers, smartphones, and mobile PCs, as well as portable game devices, power tools, electric bicycles, hybrid vehicles, electric vehicles, and power storage systems.

[0112] While preferred embodiments of this disclosure have been described above, this disclosure is not limited to the embodiments described above. [Examples]

[0113] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples.

[0114] <Example 1-1> (1) Preparation of carbon black (a-1) As carbon black (a-1), the BET specific surface area is 141.1 m². 2 Acetylene black was prepared with a density of 175.0 mg / g, an iodine adsorption capacity of 175.0 mg / g, a ratio (IV / BET) of 1.24, and an average primary particle diameter of 23 nm.

[0115] (2) Production of modified carbon black (A-1) Modified carbon black (A-1) was produced using carbon black (a-1) by the following method. A batch-type ozone treatment was performed by continuously flowing ozone-containing mixed gas onto a reaction vessel of a small rotary kiln with carbon black (a-1). The ozone-containing mixed gas injected into the kiln had an ozone concentration of 60 mg / L (ozone-containing oxygen diluted with nitrogen to adjust the oxygen concentration to 30 vol%) and was injected at a flow rate of 1 L / min in the direction of the rotation axis of the rotating kiln (rotation speed: approximately 40 rpm). The ratio (M1 / S0) of the amount of ozone supplied into the reaction vessel (M1) to the surface area (S0) of the raw material carbon black in the reaction vessel was 0.25 mg / m³. 2 The ozone supply was adjusted to produce modified carbon black (A-1). The BET specific surface area of ​​the obtained modified carbon black was 167.4 m². 2 The iodine adsorption amount was 181.0 mg / g, and the ratio (IV / BET) was 1.08.

[0116] Carbon black (a-1) and modified carbon black (A-1) were evaluated using the following method. The results are shown in Table 1. In Table 1, carbon black (a-1) is listed as Comparative Example 1-1.

[0117] (i) Temperature-controlled desorption gas analysis The following method was used to perform temperature-induced desorption gas analysis, and the release amounts of carbon dioxide, carbon monoxide, and water per unit surface area were determined. One mg of the target material (carbon black or modified carbon black) powder was weighed into a quartz dish, a quartz lid was placed on top, and the temperature was raised from room temperature to 1300°C. The desorbed gas was analyzed using a quadrupole mass spectrometer (QMS). The desorbed amounts of carbon dioxide, carbon monoxide, and water were calculated based on sensitivity correction using the ESCO method, assuming that the ion current in the mass spectrum m / z originated only from the target molecules. The calculated desorbed amount (mol / mg) was then converted to the BET specific surface area (m²) of the target material (carbon black or modified carbon black). 2 Using the value of / g, 1m 2 The amount was converted to moles per unit. Note that the amount of carbon dioxide and carbon monoxide desorbed (mol / m³) 2 The amounts were calculated from the amount of desorption from room temperature to 1300°C. Also, the amount of water desorbed (mol / m³) was calculated. 2 To exclude the effect of adsorbed moisture, the amount of desorption was calculated from the amount of desorption from 150°C to 1300°C.

[0118] (ii) Measurement of powder resistance The powder resistance (mΩ·cm) under a 20kN load was measured using the following method. A powder resistivity measurement system (product name: MCP-PD51, manufactured by Nitto Seikou Analytech Co., Ltd.) equipped with a resistivity meter (product name: Loresta GP, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) was prepared. 1 g of the target powder (carbon black or modified carbon black) was filled into the measurement container, pressurized to 20 kN, and the volume resistivity was measured. The measurement conditions were a 4-point probe, electrode spacing of 3 mm, electrode radius of 0.7 mm, and sample radius of 10 mm.

[0119] (iii) Measurement of powder density The powder density (g / cc) under a 20kN load was measured using the following method. A powder resistivity measurement system (product name: MCP-PD51, manufactured by Nitto Seikou Analytech Co., Ltd.) equipped with a resistivity meter (product name: Loresta GP, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) was used. 1 g of the target powder (carbon black or modified carbon black) was filled into a measurement container and pressurized to 20 kN. The powder density at a 20 kN load was measured from the amount of powder added and the height of compression at 20 kN pressurization.

[0120] (iv) Preparation of slurry The slurry is prepared using the following method, and the particle size (D) in the slurry is measured at each dispersion time. 50 , D 90 , D 10 Measurements were taken of the ) and the viscosity of the slurry.

[0121] <Preparation of Slurry> Hydrogenated acrylonitrile rubber (HNBR) and NMP were mixed to obtain an HNBR solution (concentration: 8% by mass). Next, 5.5 g of modified carbon black (or carbon black) and 36.8 g of the HNBR solution were added to a container and stirred at 2000 rpm for 5 minutes using a rotation / revolution mixer, Awatori Rentaro (manufactured by Shinky Co., Ltd., ARV-310). Next, 7.7 g of the HNBR solution was added to the container and stirred further at 2000 rpm for 5 minutes. Finally, 100 g of φ0.5 mm zirconia beads were added to the container and stirred with a rocking mill to obtain a slurry. The modified carbon black (or carbon black) content in the slurry was 11% by mass on a total slurry basis, and 89.92% by mass on a total solids basis. The dispersant content was 11.2 parts by mass per 100 parts by mass of modified carbon black (or carbon black). The stirring time in the rocking mill was defined as the "dispersion time," and the particle size and viscosity of the slurry were measured at each dispersion time. The slurry before adding 100g of φ0.5mm zirconia beads to the container was also measured for particle size and viscosity, assuming a dispersion time of 0 hours.

[0122] <Measurement of particle size in slurry> The volume-based particle size distribution was measured using the laser diffraction / scattering method with a particle size distribution analyzer (Microtrac MT3300EX II and USVR ultra-low volume circulator, manufactured by Microtrac Bell) in the following manner. (Measurement conditions) Measurement range: 0.02~2000μm Particle permeability: Absorption Particle shape: non-spherical Solvent: NMP Circulation output: 5 Sample input volume: Adjust to achieve the optimal concentration range (transmittance: 0.9 to 0.85) displayed when the sample is added.

[0123] (v) Preparation of coating solution for positive electrode formation The following method was used to prepare a coating solution for positive electrode formation with a solid content of 53% by mass and to measure its viscosity. In Table 1, viscosity (i) is calculated based on a shear rate of 0.1 s. -1 from 100s -1 Shear rate when increased to 10s -1 The value is shown for time, and viscosity (ii) is calculated with a shear rate of 100s. -1 from 0.1s -1 Shear rate when reduced to 10s -1 It shows the value of time.

[0124] <Preparation of coating solution for positive electrode formation> As an active material, average particle size D 50 A 10 μm lithium nickel-manganese-cobalt oxide (manufactured by Yongbai Technology Co., Ltd.), modified carbon black (or carbon black) as a conductive material, an NMP solution of polyvinylidene fluoride as a binder, and NMP as a dispersion medium were prepared. Modified carbon black (or carbon black) and an NMP solution of polyvinylidene fluoride were mixed using a rotation-and-revolution type mixer (Awatori Rentaro ARV-310, manufactured by Thinky Co., Ltd.) to obtain a mixture. Next, the mixture was mixed with the active material, and NMP was added until it reached a viscosity suitable for coating. The mixture was then mixed using the rotation-and-revolution type mixer until homogeneous to obtain a coating solution for forming the positive electrode. The amounts of each raw material were adjusted so that, based on the total amount of solids in the coating solution for forming the positive electrode, the active material was 96.0% by mass, the modified carbon black (or carbon black) was 2.0% by mass, and the binder was 2.0% by mass. Next, the coating solution for forming the positive electrode was deposited onto one side of a 15 μm thick aluminum foil (manufactured by UACJ) using an applicator to create a laminate. The laminate was then left to stand in a dryer and pre-dried at 105°C for 1 hour to completely remove the nanopolymer (NMP). After that, it was pressed and cut to obtain a positive electrode comprising a current collector and an asphalt mixture layer.

[0125] <Measurement of viscosity of coating solution for positive electrode formation> The viscosity of the coating solution for forming the positive electrode was determined using a viscoelasticity measuring device (Anton Paar, "MCR302") by the following method, with a shear rate of 10s. -1 The viscosity was measured. (Measurement conditions) Measuring jig: Cone plate (2°) Measurement temperature: 25℃ Shear rate: 100s -1 →0.1s -1 , 0.1s -1 →100s -1 Number of measurement points: 17 points Next, the preparation of the positive electrode forming coating solution and the measurement of its viscosity were carried out in the same manner as described above, except that the solid content concentration of the positive electrode forming coating solution was changed to 64%.

[0126] <Examples 1-2> The ratio (M1 / S0) of the amount of ozone supplied into the reaction vessel (M1) to the surface area (S0) of the raw material carbon black in the reaction vessel is set to 0.5 mg / m². 2 Except for the change made, modified carbon black was produced in the same manner as in Example 1-1(2) to obtain modified carbon black (A-2). The obtained modified carbon black (A-2) was evaluated in the same manner as in Example 1-1. The results are shown in Table 1.

[0127] <Examples 1-3> The ratio (M1 / S0) of the amount of ozone supplied into the reaction vessel (M1) to the surface area (S0) of the raw material carbon black in the reaction vessel is set to 0.75 mg / m². 2 Except for the change made, modified carbon black was produced in the same manner as in Example 1-1(2) to obtain modified carbon black (A-3). The obtained modified carbon black (A-3) was evaluated in the same manner as in Example 1-1. The results are shown in Table 1.

[0128] <Examples 1-4> The ratio (M1 / S0) of the amount of ozone supplied into the reaction vessel (M1) to the surface area (S0) of the raw material carbon black in the reaction vessel is set to 1.00 mg / m².2 Except for the change made to [specific component], modified carbon black was produced in the same manner as in Example 1-1(2) to obtain modified carbon black (A-4). The obtained modified carbon black (A-4) was evaluated in the same manner as in Example 1-1.

[0129] Note that "-" in the table indicates that the measurement was not taken.

[0130] [Table 1]

[0131] As shown in Table 1, the modified carbon black of the examples had a particle size (D) in the slurry. 50 The time it takes for the ratio to become 0.7 or less is shorter compared to the carbon black of Comparative Example 1-1. From this result, it was confirmed that the modified carbon black of this disclosure has excellent dispersibility and can form a slurry with a sufficiently dispersed state in a short time.

[0132] Furthermore, as shown in Table 1, the viscosity of the cathode-forming coating solution in the examples is lower compared to the case using the carbon black of Comparative Example 1-1. From these results, it was confirmed that the modified carbon black produced by the manufacturing method of this disclosure can form a cathode-forming coating solution with a high solid content at a low viscosity.

[0133] <Example 2-1> (1) Preparation of carbon black (b-1) As carbon black (b-1), the BET specific surface area is 291.0 m². 2 Acetylene black was prepared with a density of 366.0 mg / g, an iodine adsorption capacity of 366.0 mg / g, a ratio (IV / BET) of 1.26, and an average primary particle size of 19 nm.

[0134] (2) Production of modified carbon black (B-1) Modified carbon black (B-1) was obtained by producing modified carbon black in the same manner as in Example 1-1(2), except that carbon black (b-1) was used instead of carbon black (a-1).

[0135] For carbon black (b-1) and modified carbon black (B-1), a slurry was prepared using the following method, and the particle size (D) in the slurry was measured at each dispersion time. 50 , D 90 , D 10 Measurements were taken of the ) and the viscosity of the slurry. The results are shown in Table 2. In Table 2, carbon black (b-1) is listed as Comparative Example 2-1.

[0136] <Method for preparing slurry> Hydrogenated acrylonitrile rubber (HNBR) and NMP were mixed to obtain an HNBR solution (concentration: 8% by mass). Next, 5.5 g of modified carbon black (or carbon black) and 31.23 g of the HNBR solution were added to a container and stirred at 2000 rpm for 5 minutes using a rotation / revolution mixer, Awatori Rentaro (manufactured by Shinky Co., Ltd., ARV-310). Next, 13.26 g of the HNBR solution was added to the container and stirred further at 2000 rpm for 5 minutes. Finally, 100 g of φ0.5 mm zirconia beads were added to the container and stirred with a rocking mill to obtain a slurry. The modified carbon black (or carbon black) content in the slurry was 11% by mass on a total slurry basis, and 89.92% by mass on a total solids basis. The dispersant content was 19.3 parts by mass per 100 parts by mass of modified carbon black (or carbon black). The stirring time in the rocking mill was defined as the "dispersion time," and the particle size and viscosity of the slurry were measured at each dispersion time. The slurry before adding 100g of φ0.5mm zirconia beads to the container was also measured for particle size and viscosity, assuming a dispersion time of 0 hours.

[0137] <Example 2-2> The ratio (M1 / S0) of the amount of ozone supplied into the reaction vessel (M1) to the surface area (S0) of the raw material carbon black in the reaction vessel is set to 1.00 mg / m². 2 Except for the change made to [specific component], modified carbon black was produced in the same manner as in Example 2-1(2) to obtain modified carbon black (B-2). The obtained modified carbon black (B-2) was evaluated in the same manner as in Example 2-1. The results are shown in Table 2.

[0138] [Table 2]

[0139] As shown in Table 2, the modified carbon black in the examples has a particle size (D) in the slurry. 50 The time it takes for the solid content to become 0.7 or less is shorter compared to the carbon black of Comparative Example 2-1. From this result, it was confirmed that the modified carbon black of this disclosure has excellent dispersibility and can form a slurry with a sufficiently dispersed state in a short time. Furthermore, from this result and the results in Table 1, it was confirmed that the modified carbon black of Examples 2-1 and 2-2 can form a cathode forming coating solution with a high solid content concentration at a low viscosity.

Claims

1. It comprises an active material, a binder, modified carbon black, and a liquid medium. The BET specific surface area (BET(m)) of the modified carbon black 2 The ratio of iodine adsorbed (IV (mg / g)) to (IV / g) (IV / BET) is 0.70 or more and 1.20 or less. The amount of carbon dioxide emitted per unit surface area of ​​the aforementioned modified carbon black, as measured by temperature-controlled desorption gas analysis, is 2.5 × 10⁻⁶. -7 mol / m 2 That's all. The carbon monoxide emission per unit surface area of ​​the aforementioned modified carbon black, as measured by temperature-controlled desorption gas analysis, is 5.0 × 10⁻⁶. -7 mol / m 2 That's all. Coating liquid for positive electrode formation.

2. The amount of carbon dioxide emitted per unit surface area of ​​the modified carbon black, as measured by temperature-controlled desorption gas analysis, is 2.0 × 10⁻⁶. -6 mol / m 2 The following: The emission amount of carbon monoxide per unit surface area of the modified carbon black as measured by temperature-programmed desorption gas analysis is 5.0×10 -6 mol / m 2 or less, the coating liquid for forming a positive electrode according to claim 1.

3. The BET specific surface area of ​​the aforementioned modified carbon black is 120 m². 2 / g or more 500m 2 The coating liquid for forming a positive electrode according to claim 1, wherein the amount is less than or equal to / g.

4. The coating liquid for forming a positive electrode according to claim 1, wherein the modified carbon black is an ozone-treated product of acetylene black.

5. The process includes a coating liquid manufacturing step of mixing an active material, a binder, modified carbon black, and a liquid medium to obtain a coating liquid for forming a positive electrode. The BET specific surface area (BET(m)) of the modified carbon black 2 The ratio of iodine adsorbed (IV (mg / g)) to (IV / g) (IV / BET) is 0.70 or more and 1.20 or less. The amount of carbon dioxide emitted per unit surface area of ​​the aforementioned modified carbon black, as measured by temperature-controlled desorption gas analysis, is 2.5 × 10⁻⁶. -7 mol / m 2 That's all. The carbon monoxide emission per unit surface area of ​​the aforementioned modified carbon black, as measured by temperature-controlled desorption gas analysis, is 5.0 × 10⁻⁶. -7 mol / m 2 That's all. A method for manufacturing a coating solution for forming a positive electrode.

6. The aforementioned coating liquid manufacturing process, A first mixing step involves mixing the powdered modified carbon black with a binder-containing solution containing the binder and solvent to obtain a mixed solution. A second mixing step involves mixing the aforementioned mixture with the aforementioned active material to obtain the coating liquid for forming the positive electrode. The manufacturing method according to claim 5, including

7. The manufacturing method according to claim 6, wherein the second mixing step is a step of mixing the mixed liquid, the active material, and the liquid medium to obtain the coating liquid for forming the positive electrode.

8. A method for manufacturing a positive electrode, comprising the step of applying a positive electrode forming coating liquid according to any one of claims 1 to 4, or a positive electrode forming coating liquid manufactured by the manufacturing method according to any one of claims 5 to 7, onto a current collector to form a composite material layer on the current collector.

9. A step of applying a positive electrode forming coating liquid according to any one of claims 1 to 4, or a positive electrode forming coating liquid manufactured by the manufacturing method according to any one of claims 5 to 7, onto a current collector to form a composite layer on the current collector and obtain a positive electrode, The process of stacking the positive electrode and the negative electrode with a separator in between to obtain a battery, A method for manufacturing batteries, including the invention of a battery.

Citation Information

Patent Citations

  • Acetylene black, method for producing the same and use thereof

    JP2009035598A